Pengaruh Pengawasan dan Pengalaman Kerja Terhadap Kinerja Karyawan Pada PT. Mitra Karya Anugrah - Rosinta Romauli Situmeang (UII, 2017)
PT. Mitra Karya Anugrah Medan is a company engaged in the sale of motorcycle parts of Aspira brand which has some problems relating to supervision and work experience. A common issue occured wasthat the lack of oversight in the realization of sales visits to shops and many employees were those who have recently graduated from high school who do not have work experience at all. The lower in employee performance can be seen from the decline in sales revenue over the last three years. The theories used were of human resource management, which deals with supervision, work experience and employee performance. The research used a quantitative approach, with descriptive quantitative studytype and the nature is descriptive explanatory research. Data were collected through questionnaires, interviews and documentation study. The method of data analysis of this research was multiple linear regression. The population of the study were all employees at PT. Mitra Karya Anugrah Medan totaling 42 people at one time used for the study sample. To test the validity of 30 respondents of similar companies were taken from PT. Sinar Inti Cakra Medan. Results of research on this hypothesis indicated that the supervision and work experience simultaneously and partially affected employeeperformance and supervision was the most dominant factor affecting employee performance. It is concluded that simultaneously and partially, supervision and work experience have a positive and significant effect on the performance of employees at PT. Mitra Karya Anugrah Medan